Presidential decree-laws nos. 103/2012&presidential decree-laws nos. 117/2014 on amending some provisions of the built real estate taxes law issued as per law no. 196 of the year 2008 = قرارات رئيس جمهورية مصر العربية بالقوانين أرقام 103/2012 و 117/2014 بتعديل بعض أحكام قانون الضريبة على العقارات المبنية الصادر بالقانون رقم 196 لسنة 2008 - Egypt. Ministry of Finance. The Egyptian Customs Authority (2025)
Decree law of the President of the Arab Republic of Egypt no. 103 of the year 2012 on amending some provisions of the built real estate taxes law issued as per law no. 196 of the year 2008 -- Decree law of the President of the Arab Republic of Egypt no. 117 of the year 2012 on amending some provisions of the built real estate taxes law issued as per law no. 196 of the year 2008 قرار رئيس جمهورية مصر العربية بالقوانين أرقام 103 لسنة 2012 بتعديل بعض أحكام قانون الضريبة على العقارات المبنية الصادر بالقانون رقم 196 لسنة 2008 -- قرار رئيس جمهورية مصر العربية بالقوانين أرقام 117 لسنة 2012 بتعديل بعض أحكام قانون الضريبة على العقارات المبنية الصادر بالقانون رقم 196 لسنة 2008